Astenopia ocular en paciente femenino de 33 años de edad. - Peralta Menéndez, Fabiola Estefanía (2022)
Asthenopia or also known as visual fatigue, is an ocular reaction characterized by the overexertion of the ciliary muscle, since it is in charge of helping the lens to perfectly focus an image. This overexertion during the ciliary or accommodation processes occurs more frequently in those who carry out activities that require correct vision, especially close vision, for a long time, this generates stress or fatigue in the aforementioned muscle, causing the appearance of symptoms such as: blurred vision, headaches, burning, foreign body sensation, dry eye, among others, which have a certain similarity with the symptoms of hypermetropic astigmatism. As professionals responsible for primary vision care, our goal is to provide adequate diagnosis and treatment to improve the visual quality of our patients. In the present clinical case of investigation we will treat a 33-year-old female patient, who comes to the consultation referring symptoms of blurred vision with her optical correction in use, additionally indicates presenting more frequently headaches, red eye, foreign body sensation, burning, eye sequel and tearing, in the last six months. Throughout the course of the case, we discovered that our patient had not had an optometric control in the last two years, analyzing his clinical history, which indicated mild astigmatism, which led us to suspect the presence or development of astigmatism. Hypermetropic not yet detected. When carrying out the instrumental measurements, we verified the development of it in the right eye for which the use of glasses or lenses was sent for treatment.